Strengthening Student Character through Yasinan Tradition: The Role of Local Wisdom in State of Madrasah Ibtidaiyah (MIN) - Ansori, Ansori; Saifillah al-Faruq, Muhammad Sofa; Yusup, Muhammad; Setiawan, Heru; Aprianto, Iwan (EDUTEC : Journal of Education And Technology, 2025)
This study aims to analyze how the Yasinan tradition in MIN 4 Batang Hari contributes to instilling character values in students. The research method used is qualitative with a descriptive approach. Data was obtained through interviews with teachers and students, direct observation, and documentation of Yasinan's activities. The results of the study show that Yasinan activities are an effective means of shaping students' character, such as discipline, order, and other Islamic values. Teachers play a role model in guiding students, but there are several obstacles, such as lack of parental attention and the influence of social media that can affect student behavior. Therefore, synergy is needed between Madrasah and parents to optimize the formation of student character through sustainable religious activities.